Host cell factors and HIV-1 integration. (November 2007) - Engelman, Alan
Retroviral replication hinges on the formation of the provirus, the integrated product of the linear DNA that is made during reverse transcription. Integration is catalyzed by the viral recombinase integrase, yet a number of studies indicate that other viral or cellular proteins play important cofactor roles during HIV-1 integration. Some of these factors bind directly to integrase, whereas others gain access to the integration machinery by binding to the DNA or other viral proteins. This article reviews recent advances on the roles of cellular proteins in HIV-1 integration. As a number of studies have highlighted a particularly important role for the integrase interactor lens epithelium-derived growth factor (LEDGF), much of the focus will be on its mechanism of action and the potential to develop inhibitors of this crucial virus––host interaction.